Mengembangkan Kreativitas Anak Melalui Metode Proyek Pada Anak Kelompok B Di Ra Bakti Xii Wonorejo Gondangrejo Karanganyar Tahun Pelajaran 2014/2015 - Rahmawati, Anis, Dr. Darsinah, M. Si (2015)
This research's aim is to develop children's creativity through project method. This research is Classroom Action Research (CAR). The subject of this research is Group B students of RA Bakti XII Wonorejo, Gondangrejo, Karanganyar 2014/2015 Academic Year. This research is conducted in two cycles. Each cycle consists of two meetings. The data of the development of children's creativity and the conducting of project method are submitted through observation, documentation, and interview. Technique of analysis data that is used namely comparative analysis, critical, and one-way anova. Based on the results of the research, the percentage of children that achieves of growing as expected is about 36,84% in the early condition. The cycle I is 63,15% and the cycle II is 84,21%. Besides, based on the result of uji F with significant level 0,05, it can be obtained the result of Fhitung is bigger than Ftabel. It is equal to 26,271 > 3,17, so Ho is rejected and Ha is accepted. It means that there is significant difference between the result of the development of children's creativity in the early condition; cycle I and cycle II. So, based on the research, it can be concluded that project method can develop children's creativity on Group B children's in RA Bakti XII Wonorejo Gondangrejo Karanganyar 2014/2015 Academic Year.